2018
DOI: 10.2147/ijn.s175914
|View full text |Cite|
|
Sign up to set email alerts
|

Polycaprolactone electrospun fiber scaffold loaded with iPSCs-NSCs and ASCs as a novel tissue engineering scaffold for the treatment of spinal cord injury

Abstract: BackgroundSpinal cord injury (SCI) is a traumatic disease of the central nervous system, accompanied with high incidence and high disability rate. Tissue engineering scaffold can be used as therapeutic systems to provide effective repair for SCI.PurposeIn this study, a novel tissue engineering scaffold has been synthesized in order to explore the effect of nerve repair on SCI.Patients and methodsPolycaprolactone (PCL) scaffolds loaded with actived Schwann cells (ASCs) and induced pluripotent stem cells -derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 69 publications
(69 reference statements)
0
35
0
Order By: Relevance
“…The electrospinning technique to synthesize a biocompatible and biodegradable novel poly- caprolactone (PCL) scaffold was used also by Zhou et al [39]. The PCL scaffold was coated with Schwann cells and iPSC-NPCs and transplanted into in vivo SCI rat model.…”
Section: Advances In Scaffold Constructionmentioning
confidence: 99%
“…The electrospinning technique to synthesize a biocompatible and biodegradable novel poly- caprolactone (PCL) scaffold was used also by Zhou et al [39]. The PCL scaffold was coated with Schwann cells and iPSC-NPCs and transplanted into in vivo SCI rat model.…”
Section: Advances In Scaffold Constructionmentioning
confidence: 99%
“…Microenvironmental imbalances are often accompanied by increased inhibitory factors, loss of neurons, filling of glial cells and reduction of promoting factors at different times and spaces [6]. Multiple cells combined with different nutritional factors or scaffolds have become the focus of spinal cord injury repair [7]. However, treatment with cells, surgery, or medication have been unable to completely cure spinal cord injuries [8].…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H NMR, 13 C NMR, and FTIR spectra ( Figures S2, S3 and S4) indicated that the Se-CQDs had different chemical structures from those of the precursor molecule, L-selenocystine, which confirmed the chemical transformation of L-selenocystine into Se-CQDs. The XPS spectrum indicated that the Se-CQDs were mainly composed of carbon, nitrogen, selenium, and oxygen, which corresponded to the typical peaks of C 1s, N 1s, O 1s, and Se 3d ( Figure 2C).…”
mentioning
confidence: 94%
“…4,5,11 Immediately after the primary injury, a sustained secondary injury cascade occurs, which leads to further damage to the spinal cord and neurological dysfunction. 4,5,[10][11][12][13] Thus, it is of great importance to mitigate secondary injury in the clinical treatment of acute TSCI. Currently, high-dose administration of methylprednisolone sodium succinate is the only recommended neuroprotective drug available for ameliorating secondary injury after acute TSCI.…”
Section: Introductionmentioning
confidence: 99%